2002
DOI: 10.1007/s003830100699
|View full text |Cite
|
Sign up to set email alerts
|

Lichen sclerosus et atrophicus in children with phimosis and hypospadias

Abstract: This prospective study was designed to evaluate the incidence of lichen sclerosus et atrophicus (LSA) in a pediatric population with hypospadias and phimosis in order to discuss the indications for circumcision and utilization of preputial skin for urethral surgery. All 115 boys, 55 with congenital phimosis, 45 with acquired phimosis, 13 with hypospadias, and 2 with recurrent chronic balanitis, underwent full-thickness biopsies of the foreskin that were examined by a single pathologist. Of the patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 0 publications
3
39
0
3
Order By: Relevance
“…96 BXO is thought to account for 4-15% of the strictures that occur after hypospadias repairs in which the urethroplasty is performed using a prepucial flap or graft. 97,98 Substitution urethroplasty with oral mucosa is mandatory in the presence of BXO. 98,99 Urethral diverticula Dilation of the neourethra (Figure 4), also known as megalourethra, has been described after the correction of proximal hypospadias, 100,101 although only for flap tube repairs.…”
Section: Urethral Stricturementioning
confidence: 99%
“…96 BXO is thought to account for 4-15% of the strictures that occur after hypospadias repairs in which the urethroplasty is performed using a prepucial flap or graft. 97,98 Substitution urethroplasty with oral mucosa is mandatory in the presence of BXO. 98,99 Urethral diverticula Dilation of the neourethra (Figure 4), also known as megalourethra, has been described after the correction of proximal hypospadias, 100,101 although only for flap tube repairs.…”
Section: Urethral Stricturementioning
confidence: 99%
“…[95] A further study found LS in 60% of boys with acquired phimosis and in 30% of those with congenital phimosis. [96] Foreskin inflammation was seen in 88% and 82%, respectively. The study also examined boys with congenital hypospadias, with 61% showing symptoms of inflammation and 15% having features consistent with LS.…”
Section: Resultsmentioning
confidence: 99%
“…Meatal or urethral involvement is more likely with a history of previous surgery and was seen in 27% in the series by Gargollo et al [168]. The incidence of this condition is underestimated and recent evidence suggests that in boys referred with a diagnosis of phimosis the incidence ranges between 10-40 % [169][170][171][172]. In a series of 100 boys referred for phimosis, the incidence of LS was 1.8% under 6 years of age and up to 21% in those older [171].…”
Section: Genital Lichen Sclerosismentioning
confidence: 97%